Plasma levels of the interleukin-6 cytokine family in persons with severe Plasmodium falciparum malaria - Christoph Wenisch (2018)
Plasma levels of interleukin (IL)-6, soluble IL-6 receptor, soluble gp130, leukemia inhibitory factor (LIF), and ciliary neutrophic factor (CNTF) were analyzed in 32 patients with severe malaria. Ten had renal failure, 8 had cerebral malaria, and 14 had other causes of severity. Before treatment, the IL-6 and soluble IL-6 receptor plasma levels were significantly higher in persons with cerebral malaria or renal failure than in other groups (P< .01 for both). After initiation of therapy, IL-6 levels dropped within 24 h, but soluble IL-6 receptor levels increased. CNTF levels were significantly reduced in persons with cerebral malaria or renal failure but normalized within 24 h. Plasma concentrations of gp130 and LIF did not differ between the malaria groups or normal controls. Excessive levels of IL-6 could be controlled by a subsequent shedding of the soluble IL-6 receptor, and low- level CNTF expression could contribute to or even result from cerebral malaria or renal failure.